Comparative Law Study: Sentencing of Sexual Violence Perpetrators Who have Deviant Sexual Behavior - Mardin, Nurhayati; Purnamasari, Andi Intan; Miqat, Nurul; Kharismawan, Adiguna; Nur, Rafika (Jambura Law Review, 2022)
The purpose of this paper is to find the ideal form of punishment for perpetrators of sexual violence who suffer from deviant sexual behavior. The method in this study is a normative legal research type, where activities are carried out by researching and analyzing the forms of sanctions and punishments regulated in positive law, in addition to conducting a comparative study of the provisions in positive law in Indonesia in the perspective of the types of sanctions against perpetrators of sexual violence crimes. who suffer from deviant sexual behavior. The results show that the ideal form of sanctions imposed on perpetrators of sexual violence who suffer from deviant sexual behavior should not only focus on imprisonment, however, it must be accompanied by other treatments or actions to treat the deviations in sexual behavior he suffers as mandated in the Sexual Violence Criminal Act, which is to combine imprisonment and special rehabilitation to cure his sexual behavior deviations. With the imposition of imprisonment alone, it will not be able to treat the main factor that triggers sexual violence crimes committed by perpetrators who suffer from deviant sexual behavior, so that rehabilitation or treatment efforts are important things that must be done so that there is no repeated or recidive crime.